Pengaruh Therapeutic Exercise Walking terhadap Sirkulasi Darah Perifer pada Pasien Diabetes Melitus Tipe 2 di Kelurahan Gebang Kecamatan Patrang Kabupaten Jember - Erti Ikhtiarini Dewi; Amadea Yollanda; Nur Widayati; Rondhianto Rondhianto (UPT Percetakan dan Penerbitan Universitas Jember, 2020)
Pathological change experienced by patients with type 2 diabetes mellitus is impaired peripheral blood circulation, especially in the lower limbs and feet. Peripheral blood circulation can be examined by measuring Ankle Brachial Index (ABI). Therapeutic exercise walking is one of physical activities which can improve blood circulation. This research goal was to analyze the effect of therapeutic exercise walking on peripheral blood circulation in patients with type 2 diabetes mellitus. The research design was randomized control group pretest-posttest design. The sample size was 15 respondents as control group and 15 respondents as treatment group. Data was analyzed by using dependent t-test and independent t-test with significant level of 0.05. This result showed a significant increase of ABI after therapeutic exercise walking in the treatment group (p= 0.001). However there was a significant decrease of ABI between pretest and posttest in control group (p=0.010).Independent t-test indicated a significant difference of ABI between treatment group and control group (p=0.000). So, it can be concluded that there is an influence of therapeutic exercise walking on the peripheral blood circulation in patients with type 2 diabetes mellitus. Nurses should apply therapeutic exercise walking to improve peripheral blood circulation in patients with type 2 diabetes mellitus. Keywords: type 2 diabetes mellitus, therapeutic exercise walking, ankle brachial index